Laser direct synthesis of silicon nanowire field effect transistors. (15th January 2015) - Nam, Woongsik; Mitchell, James I; Ye, Peide D; Xu, Xianfan
Abstract: We demonstrate a single-step, laser-based technique to fabricate silicon nanowire field effect transistors. Boron-doped silicon nanowires are synthesized using a laser-direct-write chemical vapor deposition process, which can produce nanowires as small as 60 nm, far below the diffraction limit of the laser wavelength of 395 nm. In addition, the method has the advantages of in situ doping, catalyst-free growth, and precise control of nanowire position, orientation, and length. Silicon nanowires are directly fabricated on an insulating surface and ready for subsequent device fabrication without the need for transfer and alignment, thus greatly simplifying device fabrication processes. Schottky barrier nanowire field effect transistors with a back-gate configuration are fabricated from the laser-direct-written Si nanowires and electrically characterized.